Polymer Electrolyte Membrane Fuel Cell Performance of a Sulfonated Poly(Arylene Ether Benzimidazole) Copolymer Membrane - Hasan Ferdi Gerçel; Çağla Gül Tosun; Levent Akyalçın (Advances in Materials Science and Engineering)
Disodium-3,3′-disulfonate-4,4′-dichlorodiphenylsulfone (SDCDPS) and 5,5′-bis[2-(4-hydroxyphenyl)benzimidazole] (HPBI) monomers were synthesized. Binding these monomers via nucleophilic aromatic polycondensation reaction, a sulfonated poly(arylene ether benzimidazole) copolymer was synthesized. Structures of monomers and copolymer were confirmed by proton nuclear magnetic resonance spectroscopy (1H NMR) and Fourier transform infrared (FTIR) spectroscopy analyses. Proton exchange membrane was prepared by dissolving copolymer in dimethylacetamide (DMAc) and casting onto a glass plate. Copolymer membrane was doped with sulfuric acid to ensure proton exchange character. Single cell performance of the copolymer membrane was tested in a polymer electrolyte membrane fuel cell test station. The highest power density of the membrane was measured as 23.7 mW cm−2 at 80°C. Thermogravimetric analysis (TGA) showed that as the degree of disulfonation is increased thermal stability of the copolymer is increased.